2016
DOI: 10.1177/1558944716668824
|View full text |Cite
|
Sign up to set email alerts
|

Drill Penetration Injury to Extensor Tendons: A Biomechanical Analysis

Abstract: Background: Little is known about extensor tendon failure following drill injury at the time of volar plate fixation. Our goals were to analyze extensor tendon injury following simulated drill penetration, and change in tendon displacement during cyclic loading following simulated drill penetration injury. Methods: Extensor pollicis longus (EPL) and extensor carpi radialis brevis (ECRB) tendons were harvested from 9 fresh frozen cadaveric arms. Eighteen EPL and 18 ECRB samples were created from harvested tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, the quantity of tendon damage may not be of clinical relevance or require further clinical reconstruction (Colzani et al, 2016). In-vitro studies have shown that extensor tendon rupture after drill injury is rare and even lacerations of up to 75% may not fail under physiological load (Mahylis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the quantity of tendon damage may not be of clinical relevance or require further clinical reconstruction (Colzani et al, 2016). In-vitro studies have shown that extensor tendon rupture after drill injury is rare and even lacerations of up to 75% may not fail under physiological load (Mahylis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Multiple studies demonstrate plates to have higher breaking strength than HCS. 25,31,35 Melamed et al found an average load of failure in 2.4 mm IM screw of 75 ± 20 N in human cadaveric bone models. 30 This is compared with an average load of failure of over 200 N in 1.5 mm, 2.0 mm, locking, and nonlocking plate constructs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that extensor tendon rupture after drill injury is rare, and even lacerations of up to 75% may not fail under physiological load. 31 …”
Section: Pearls and Pitfallsmentioning
confidence: 99%
“…The 2 reasons for irritation of the EPL resulting in tendon rupture have been reported to be a prominent screw or perforation of the dorsal surface intraoperatively with a drill bit [16,20,21]. When the patients visited our outpatient clinic with EPL tendon rupture, we conducted plain radiography and ultrasonography to confirm tendon rupture and determine whether screw penetration was present.…”
Section: Discussionmentioning
confidence: 99%